Design and Implementation Of A Smart Stick and An Alert Device For People With Visual Impairment - Atyaf Ayman Euyz Hashem; Duaa Hassan Hamza Ali; Ruqaya Hassan Abdul Amir Mohammed Saleh; Ahmed Abdel Hadi Mohammed Reda Ali; Tamara Ali Abd Al Ameer Abd Ali (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Electronic cane: It is an electronic cane designed in the shape of a long white cane, but it provides the blind with ultrasonic frequencies that he can feel under his hand and through an audible alarm when it hits a certain obstacle in its path1. It can also detect obstacles in all directions at a distance of five meters. The ends of this cane are made of lead. The International Federation of the Blind, which is one of the organizations affiliated with the United Nations, has declared October 15 of each year as the International Day of the White Cane for the Blind, due to the utmost importance of the white cane for the blind, as it makes him depend on himself after God. This dependence is foldable and is stronger and lasts for a long time. It is important to note here that the white cane with a red stripe placed on the lower part of the cane symbolizes the person's suffering from loss of vision with deafness or hearing impairment. Regardless of the type and shape of the white cane, it has become a symbol of the blind person’s independence and his ability to move, work and integrate into society like other individuals. It guides him to directions, barriers and obstacles and spares him the need to touch things that may be difficult or dangerous to touch, thus protecting him from many harms, in addition to providing him with a lot of information that he lacks due to his lack of sight and the inability of the other senses to provide him with it.